2023
DOI: 10.1021/acsami.3c02833
|View full text |Cite
|
Sign up to set email alerts
|

Toward On-Chip Multisensor Arrays for Selective Methanol and Ethanol Detection at Room Temperature: Capitalizing the Graphene Carbonylation

Maxim K. Rabchinskii,
Victor V. Sysoev,
Alexey S. Varezhnikov
et al.

Abstract: The artificial olfaction units (or e-noses) capable of room-temperature operation are highly demanded to meet the requests of society in numerous vital applications and developing Internet-of-Things. Derivatized 2D crystals are considered as sensing elements of choice in this regard, unlocking the potential of the advanced e-nose technologies limited by the current semiconductor technologies. Herein, we consider fabrication and gas-sensing properties of On-chip multisensor arrays based on a hole-matrixed carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
2
5
0
Order By: Relevance
“…Extrapolating the acquired SNR(C) towards the cap of SNR = 3, corresponding to the minimum practical level of signal detection, the limit of detection (LOD) was determined to be 5.1 ppm, 3.6 ppm, and 1.3 ppm for NH 3 , C 2 H 5 OH, and H 2 O, respectively. These values are among the most commonly reported for state-of-the-art graphene-based gas-sensing devices (Supplementary Materials, Section S6) and already fit almost all practical demands for the detection of ammonia and alcohols [7,8,[14][15][16]18,27,[79][80][81]. To further manifest the operation of the fabricated multisensor chips under various conditions, the chemiresistive response of the on-chip sensor arrays composed of AmG and Am-ZnO layers toward NH3 and C2H5OH mixed with humid air was recorded and examined.…”
Section: Gas-sensing Performance Of the On-chip Multisensor Arrays Co...supporting
confidence: 52%
See 2 more Smart Citations
“…Extrapolating the acquired SNR(C) towards the cap of SNR = 3, corresponding to the minimum practical level of signal detection, the limit of detection (LOD) was determined to be 5.1 ppm, 3.6 ppm, and 1.3 ppm for NH 3 , C 2 H 5 OH, and H 2 O, respectively. These values are among the most commonly reported for state-of-the-art graphene-based gas-sensing devices (Supplementary Materials, Section S6) and already fit almost all practical demands for the detection of ammonia and alcohols [7,8,[14][15][16]18,27,[79][80][81]. To further manifest the operation of the fabricated multisensor chips under various conditions, the chemiresistive response of the on-chip sensor arrays composed of AmG and Am-ZnO layers toward NH3 and C2H5OH mixed with humid air was recorded and examined.…”
Section: Gas-sensing Performance Of the On-chip Multisensor Arrays Co...supporting
confidence: 52%
“…AmG and Am-ZnO layers were placed over the on-chip multisensor arrays by spray coating according to protocols described elsewhere [27,28]. Both chips were cut from Si/SiO 2 substrate at 9 × 10 mm 2 in size, to be metalized with an array of 39 co-planar strip Pt (in the case of AmG) or Au (in the case of Am-ZnO) electrodes (50 µm wide, with 50 µm gaps) via magnetron sputtering (Emitech K575X, Ashford, Kent, UK) and photolithography patterning.…”
Section: Fabrication Of Graphene-based On-chip Multisensor Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [16], with large area flakes or wafer-scale MoS 2 grown by chemical vapour deposition. Furthermore, the layer-thickness-dependent sensitivity can be explored in future studies.…”
Section: Sensing Performancementioning
confidence: 99%
“…Beyond these materials, two-dimensional (2D) materials have emerged as promising candidates for sensing applications in recent years due to their high surface-to-volume ratio and the presence of dangling bonds on their surfaces and edges, making them ideal materials for physisorptionand chemisorption-based sensors. Apart from graphene [14][15][16], there are a variety of 2D semiconductors used for gas sensing [17], such as molybdenum disulfide (MoS 2 ) [18,19], molybdenum diselenide (MoSe 2 ) [20], molybdenum ditelluride (MoTe 2 ) [21], tungsten disulfide (WS 2 ) [22], tungsten diselenide (WSe 2 ) [23], and germanium selenide (GeSe) [24]. Suh et al showed that a pristine MoS 2 -based sensor at 110 • C has a response to 500 ppm ethanol gas with 25% responsivity [25], and Chen et al reported that a MoS 2 gas sensor detected 40 ppm ethanol, acetone, toluene, and hexane gases with responses of 11%, 12%, 6%, and 4%, respectively [26].…”
Section: Introductionmentioning
confidence: 99%